1998
DOI: 10.1046/j.1526-4610.1998.3801023.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors of Early Life as Predictors of Headache in Children at School Entry

Abstract: To study the main predictors of childhood preschool headache, 1443 families expecting their first child were followed from the onset of pregnancy to the child's sixth year of life. Subject selection was based on stratified randomized cluster sampling. Of the children, 14.9% (144) suffered from headache disturbing daily activities at the age of 6 years. The mother's assessment of the infant's poor health (OR 2.5, 95% CI 1.1 to 5.8) and feeding problems (OR 1.9, 95% CI 1.1 to 3.2) at the age of 9 months predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
1
11

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 13 publications
7
55
1
11
Order By: Relevance
“…In accordance with previous reports [8,12], headache in the present study occurred as often in girls as it did in boys at preschool age. The occurrence of headache disturbing everyday life in more than one-fourth of children aged 7 years might sound alarming.…”
Section: Discussionsupporting
confidence: 94%
“…In accordance with previous reports [8,12], headache in the present study occurred as often in girls as it did in boys at preschool age. The occurrence of headache disturbing everyday life in more than one-fourth of children aged 7 years might sound alarming.…”
Section: Discussionsupporting
confidence: 94%
“…Guidetti et al found increase in frequency and/ or severity in 45% cases of primary headache. 20 Like the present study, previous studies have reported a high frequency of headache in family members of headache suffering children [21][22] and described highest prevalence of headache in their mothers or vice versa 1 . Diagnosis of headache also influenced the family history as migraineurs had the highest prevalence of headache in their family as compared to other headache sufferers.…”
Section: Discussionsupporting
confidence: 69%
“…65 These associations remain controversial because of the variability of case definitions. Authors have used terms such as the periodic syndrome, abdominal migraine, and cyclic vomiting with imprecision.…”
Section: Historical Featuresmentioning
confidence: 99%